Fire safe epoxy composite with low dielectric properties from a combination of fluoro-phosphonium salt, melamine and copper hydroxystannate. (August 2022) - Huang, Zhenyu; Drigo, Nikita; Wang, Zhengzhou; Zhao, Ruohan; Lehner, Sandro; Jovic, Milijana; Gaan, Sabyasachi
Highlights: A novel fluorine containing phosphonium salt tetraphenylphosphine hexafluorophosphate flame retardant was synthesized. Tetraphenylphosphine hexafluorophosphate prevented dripping of epoxy system. Epoxy composites reached V0 rate at very low phosphorus loadings with melamine and copper hydroxystannate as co-additives. Cone calorimeter coupled with FTIR method was adopted to observe the reduction of heat release rate and toxic gases intensity. Epoxy composites showed lower dielectric constant and dielectric loss. Abstract: A phosphorus-fluorine containing compound tetraphenylphosphine hexafluorophosphate (Ph4 PPF6 ) was synthesized by one-step method and characterized by FTIR, NMR, SEM, and EDX. Epoxy resin (EP) cured with an aliphatic hardener and Ph4 PPF6 as a multifunctional additive were fabricated. The combined effects of Ph4 PPF6 with melamine (MEL) and copper hydroxystannate (CuHS) on the fire safety, thermal stability, smoke toxicity and dielectric performances of EP were investigated. It is found that EP containing 2 wt% P (from Ph4 PPF6 ) combined with 10 wt% MEL (sample EP 2P 10M) and EP with 2 wt% P from Ph4 PPF6 combined with 5 wt% MEL, 5 wt% CuHS (sample EP 2P 5M5C) pass V0 classification in UL-94 VB tests. The cone calorimetric tests on these composites reveal that the peak heat release rate of sample EP 2P 5M5C is reduced by 64.2% in comparison to pure EP. The toxic gases including HF, CO, HCN are reduced to different extent when MEL and CuHS used as co-additives. The dielectric loss of sample EP 2P 10M is reduced by 26.3% in comparison to pure EP.